2009
DOI: 10.1534/genetics.108.099986
|View full text |Cite
|
Sign up to set email alerts
|

A Screen for Modifiers of Notch Signaling Uncovers Amun, a Protein With a Critical Role in Sensory Organ Development

Abstract: Notch signaling is an evolutionarily conserved pathway essential for many cell fate specification events during metazoan development. We conducted a large-scale transposon-based screen in the developing Drosophila eye to identify genes involved in Notch signaling. We screened 10,447 transposon lines from the Exelixis collection for modifiers of cell fate alterations caused by overexpression of the Notch ligand Delta and identified 170 distinct modifier lines that may affect up to 274 genes. These include genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 113 publications
2
30
0
Order By: Relevance
“…We found the GMR>Dl flies not only show the eye phenotype as previously reported (Shalaby et al, 2009; data not shown), but also display a wing phenotype. In most cases, the distal part of vein L5 was lost in the GMR>Dl wings ( Figure 1C and D), as compared to the wild-type control ( Figure 1A and B).…”
Section: Resultssupporting
confidence: 90%
“…We found the GMR>Dl flies not only show the eye phenotype as previously reported (Shalaby et al, 2009; data not shown), but also display a wing phenotype. In most cases, the distal part of vein L5 was lost in the GMR>Dl wings ( Figure 1C and D), as compared to the wild-type control ( Figure 1A and B).…”
Section: Resultssupporting
confidence: 90%
“…While a number of screens have already made use of the Df collection (Bonds et al 2007) or the transposon insertion collection (Kankel et al 2007;Chang et al 2008;Shalaby et al 2009) individually, the logistics of obtaining and screening all of the 16,000 lines is not feasible for many labs. Thus, we applied a hierarchical strategy for our screen ( Figure 1A) that would take advantage of both collections and also would assay LOF vs. neomorphic effects.…”
Section: Resultsmentioning
confidence: 99%
“…The collection of deletions (Dfs; Parks et al 2004) was used for the primary screen, while the collection of transposon insertions (Thibault et al 2004) was utilized for the secondary screens. The use of these strains for genome-wide genetic interaction screening has been previously described (Kankel et al 2007;Chang et al 2008;Shalaby et al 2009). To confirm candidate interactors, all interacting transposons were crossed in at least two separate experiments to GMR-GAL4, UAS-CLASP-GFP and eye phenotypes were examined and imaged.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic and environmental factors thus likely shift the intrinsic duration or strength of Notch signaling, altering mutation tolerance in different individuals. Indeed, screens for modifiers of Notch-dependent phenotypes or signaling per se in Drosophila (Go and Artavanis-Tsakonas, 1998;Shalaby et al, 2009), mouse (Rubio-Aliaga et al, 2007 and in vitro (Mourikis et al, 2010) have revealed many candidate modifiers of Notchdependent disease. For example, loss of Itch (a negative regulator of Notch signaling) in mice interacts with gain of Notch1 in developing thymocytes to produce autoimmune disease, while loss of one allele of Dll3 in Notch1 heterozygous mice results in axial segmentation defects in 30% of double heterozygous mice (Loomes et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%